Strategic planning and quality of the educational service in the students of the Faculty of Psychology of the Federico Villarreal University. - Coronel Tello, Ana Eylin (2020)
To reach the quality of education, we must consider that, the most important thing is customer satisfaction, with the lowest possible cost, that the quality process begins with the detection of problems and limitations by the managers of the campuses since quality management is based on the continuous development of comprehensive plans, not on the execution of simple isolated or specific actions. Investigate the objective: Determine the relationship between strategic planning and the quality of educational service in students of the Faculty of Psychology of the Federico Villarreal University. The work sample consisted of 168 students to whom two questionnaires were applied to measure the variables strategic planning and quality of the educational service, instruments that passed through the validity of expert judgment and reliability through a pilot sample. The results were analyzed using the Excel spreadsheet and the SPSS statistical program. At the descriptive level, statistical tables and ranges have been used to determine the predominant levels of the variables; At the inferential level, the parametric statistics, Pearson's r, were used at a significance level of 0.05. The results found show that strategic planning is directly, moderately and significantly related to the quality of educational service in students. student subjects of the study sample. Likewise, the strategic planning is shown to correlate significantly with all dimensions of the quality of the educational service.